Integrated lipidomic and transcriptomic analysis reveals diacylglycerol accumulation in olive of Longnan (China) - Hu, Wei; Ma, Junyi; Zhang, Hongjie; Miu, Xin; Miao, Xin; Deng, Yu (PeerJ (San Francisco, CA), 2023)
Olive (Olea europaea L.) oil accumulate more diacylglycerols (DAG) than mostly vegetable oils. Unsaturated fatty acids-enriched DAG consumption enhanced wellness in subjects. However, the mechanism of DAG accumulation is not yet fully understood.BackgroundOlive (Olea europaea L.) oil accumulate more diacylglycerols (DAG) than mostly vegetable oils. Unsaturated fatty acids-enriched DAG consumption enhanced wellness in subjects. However, the mechanism of DAG accumulation is not yet fully understood.In this study, gene network of DAG accumulation and fatty acid composition in the two olive mesocarps ("Chenggu 32" (CG) and "Koroneiki" (QJ)) were investigated by integrating lipidome and transcriptome techniques.MethodsIn this study, gene network of DAG accumulation and fatty acid composition in the two olive mesocarps ("Chenggu 32" (CG) and "Koroneiki" (QJ)) were investigated by integrating lipidome and transcriptome techniques.A total of 1,408 lipid molecules were identified by lipidomic analysis in olive mesocarp, of which DAG (DAG36:3, DAG36:4 and DAG36:5) showed higher content, and triacylglycerols (TAG54:3, TAG54:4) exhibited opposite trend in CG. Specifically, DAG was rich in polyunsaturated fatty acids (especially C18:2) at the sn-2 position, which was inconsistent with TAG at the same positions (Primarily C18:1). Transcriptomic analysis revealed that phospholipase C (NPC, EC 3.1.4.3) were up-regulated relative to QJ, whereas diacylglycerol kinase (ATP) (DGK, EC 2.7.1.107), diacylglycerol acyltransferase (DGAT, EC 2.3.1.20), and phospholipid: diacylglycerol acyltransferase (PDAT, EC 2.3.1.158) were down-regulated.ResultsA total of 1,408 lipid molecules were identified by lipidomic analysis in olive mesocarp, of which DAG (DAG36:3, DAG36:4 and DAG36:5) showed higher content, and triacylglycerols (TAG54:3, TAG54:4) exhibited opposite trend in CG. Specifically, DAG was rich in polyunsaturated fatty acids (especially C18:2) at the sn-2 position, which was inconsistent with TAG at the same positions (Primarily C18:1). Transcriptomic analysis revealed that phospholipase C (NPC, EC 3.1.4.3) were up-regulated relative to QJ, whereas diacylglycerol kinase (ATP) (DGK, EC 2.7.1.107), diacylglycerol acyltransferase (DGAT, EC 2.3.1.20), and phospholipid: diacylglycerol acyltransferase (PDAT, EC 2.3.1.158) were down-regulated.We speculated that the non-acyl coenzyme A pathway played a significant role in DAG biosynthesis. Additionally, fatty acyl-ACP thioesterase B (FATB, EC 3.1.2.14), stearoyl [acyl-carrier-protein] 9-desaturase (SAD, EC 1.14.19.2) and omega-6 fatty acid desaturase (FAD2, EC 1.14.19.6) were highly expressed in CG and may be involved in regulating fatty acid composition. Meanwhile, phospholipase A1 (LCAT, EC 3.1.1.32) involved in the acyl editing reaction facilitated PUFA linkage at the sn-2 position of DAG. Our findings provide novel insights to increase the DAG content, improve the fatty acid composition of olive oil, and identify candidate genes for the production of DAG-rich oils.ConclusionWe speculated that the non-acyl coenzyme A pathway played a significant role in DAG biosynthesis. Additionally, fatty acyl-ACP thioesterase B (FATB, EC 3.1.2.14), stearoyl [acyl-carrier-protein] 9-desaturase (SAD, EC 1.14.19.2) and omega-6 fatty acid desaturase (FAD2, EC 1.14.19.6) were highly expressed in CG and may be involved in regulating fatty acid composition. Meanwhile, phospholipase A1 (LCAT, EC 3.1.1.32) involved in the acyl editing reaction facilitated PUFA linkage at the sn-2 position of DAG. Our findings provide novel insights to increase the DAG content, improve the fatty acid composition of olive oil, and identify candidate genes for the production of DAG-rich oils.